Potato seed system intervention workshop report - Borus, D.; Parker, M. (2020)
Potato is among the four crops in Kenya’s Big Four Agenda. It is grown at altitudes of 1,500 to 3,000 metres above sea level (m.a.s.l.) by an estimated 800,000 farmers on approx. 161,000 hectares. Annual production stands at approximately three million tonnes over two growing seasons, with an annual value of KES 50 billion (500 million USD). Beyond the farm, the industry employs about 3.3 million people as market agents, transporters, processors, vendors and exporters. Potato is basically a cash crop for smallholders and the second most important food crop playing a critical role in national food and nutrition security with a value of about KES of 50 billion KES (500 million USD) annually. National yields average is 8-12 t/ha, at least half the potential mainly as a consequence of limited access to quality seed coupled with other constraints. Kenya has the best-developed seed system in sub-Saharan Africa (aside from South Africa), yet the seed sector still struggles to meet the growing demand for seed. If Kenya has to increase potato productivity, then enhanced seed production and access is critical. Several programs and donors support seed system development at various levels, including the Kenya Climate Smart Agriculture Project (KCSAP), the National Agricultural and Rural Inclusive Project (NARIGP), International Potato Center (CIP), Netherlands Development Organization (SNV), German Agency for International Cooperation (GIZ) and Syngenta Foundation for Sustainable Agriculture (SFSA). Alignment and consistency in approaches among the several interventions supporting potato seed system development are critical to increasing use of improved seed and consequently increasing potato productivity. Seed system development is not only about quality-assured production, but also planning to ensure production is economically viable, especially in regard to number of multiplications and sufficient land for rotation. Critical to the interventions is to ensure the target user – farmers, particularly smallholder farmers, have reliable and equitable access to seed.